2015
DOI: 10.4172/2161-0487.1000195
|View full text |Cite
|
Sign up to set email alerts
|

When Cyberbullying and Bullying Meet Gaming: A systemic Review of the Literature

Abstract: Bullying is an increasingly growing concern among children and adolescents; with the technology advances, youth has found more efficient ways to inflict harm to others via cyberbullying. The media is a relentless source for blaming violent video games as the 'cause' of bullying and cyberbullying. Despite this vast amount of research in all three individual areas, namely bullying, cyberbullying, and gaming, there is little research reviewing the connections between them. This study, therefore, systematically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Abeele and Cock (2013) reviewed previous research and identified two different types of cyberbullying: direct virtual bullying of the victim (e.g., sending threatening messages directly to the victim) and indirect or relational cyber bullying (e.g., gossiping without the victim's knowledge). Furthermore, Qing (2015) suggests that new forms of technology pose further challenges for defining cyberbullying. Inconsistencies in study results can lead to inaccurate estimates of the prevalence of cyberbullying.…”
Section: Introductionmentioning
confidence: 99%
“…Abeele and Cock (2013) reviewed previous research and identified two different types of cyberbullying: direct virtual bullying of the victim (e.g., sending threatening messages directly to the victim) and indirect or relational cyber bullying (e.g., gossiping without the victim's knowledge). Furthermore, Qing (2015) suggests that new forms of technology pose further challenges for defining cyberbullying. Inconsistencies in study results can lead to inaccurate estimates of the prevalence of cyberbullying.…”
Section: Introductionmentioning
confidence: 99%